2001
DOI: 10.1046/j.1528-1157.2001.416800.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Valproate and Lamotrigine Treatment May Be a Marker for Reduced Growth and Bone Mass in Children with Epilepsy

Abstract: Summary:Purpose: To determine whether long-term treatment with valproate (VPA) and/or lamotrigine (LTG) in children with epilepsy is associated with altered growth and/or bone metabolism.Methods: Twenty-seven boys and 26 girls, aged 3 to 17 years (9.2 ± 3.9, mean ± SD), with epilepsy treated with VPA and/or LTG for Ն2 years were evaluated for growth, nutrient intakes, physical activity, bone mineral density (BMD), and blood biochemical indices of mineral and bone metabolism.Results: Twenty-three (43.4%) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
134
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 36 publications
(45 reference statements)
11
134
3
2
Order By: Relevance
“…Previous clinical studies demonstrated that lamotrigine did not adversely affect bone metabolism (16, 27, 36), except in combination with valproate (14). In support of this finding, lamotrigine treatment did not affect bone strength, BMD, or bone turnover in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Previous clinical studies demonstrated that lamotrigine did not adversely affect bone metabolism (16, 27, 36), except in combination with valproate (14). In support of this finding, lamotrigine treatment did not affect bone strength, BMD, or bone turnover in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…17,34,36,38,39 These latter studies found this to be the case for non-enzyme-inducing anticonvulsants (valproic acid) use 36,38 or new anticonvulsants (lamotrigine, topiramate, oxcarbazepine, sulthiamine). 17,39 In this study, none of the subjects had vitamin D deficiency, but we found higher prevalence of vitamin D insufficiency in epileptic children (39%) compared to control subjects (13%). Other studies showed a variety of results on the prevalence of vitamin D deficiency in epileptic children using long-term anticonvulsants.…”
Section: Discussionmentioning
confidence: 94%
“…13 The long-term use of anticonvulsants has been associated with increased incidence of rickets or osteomalacia, increased risk of fracture, and reduced bone mineral density. [13][14][15][16][17][18][19][20] All these conditions are associated with vitamin D deficiency. 13,15 The effects of anticonvulsants on vitamin D levels have been studied for 40 or more years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is still considered an important mechanism, later studies have shown that AEDs may cause bone loss even in the absence of vitamin D deficiency (Farhat et al, 2002;Andress et al, 2002). Furthermore, valproate, a CYP450 inhibitor, has also been shown to have an adverse effect on bone health, probably via completely different mechanisms (Sheth et al, 1995;Sato et al, 2001;Guo et al, 2001;. Decreased intestinal absorption of calcium, resistance to parathyroid hormone, calcitonin deficiency, interference with vitamin K metabolism, and a direct drug-effect on bone cell functions have also been suggested as possible mechanisms (Feldkamp et al, 2000;Petty et al, 2007).…”
Section: Effects On Bone Metabolismmentioning
confidence: 99%